A novel allele, HLA‐C*15:227, identified when typing COVID‐19 patients. (8th February 2021) - Cheranev, Valery; Loginova, Maria; Jankevic, Tatjana; Kutyavina, Svetlana; Rebrikov, Denis
Abstract : HLA‐C*15:227 differs from HLA‐C*15:02:01:01 by a single nonsynonymous change (368A → G Tyrosine 99 to Cysteine).